Multi-index Experimental Study on the Effects of Antarctic Krill oil on the Immune Function of Mice - Hasson, Ramzi; Harris, Keil; Swift, Cobi (International Journal of Agriculture and Food Sciences Research, 2024)
The aim of this study was to investigate the effects of the contents of immunity-enhancing soft capsules with krill oil as the main active ingredient on the immune function of female ICR mice. Methods: A 30-day continuous gavage experiment was performed by setting different doses of subjects, including high, medium and low dose groups and edible vegetable oil control group. During the experiment, a variety of immunological detection methods including carbon clearance test, delayed-type allergic reaction (DTH) test, antibody-producing cell test (hemolytic plaque number) and serum hemolysin were used to comprehensively evaluate the effect of the test substance on the immune function of mice. Results: In the carbon clearance test, the optical density OD(2min and 10min), liver weight, spleen weight and phagocytic index A of mice in each dose group were significantly higher than those in the control group (P < 0.05), suggesting that the subjects could enhance the phagocytic function of mice. DTH test results showed that the weight ratio of left and right ears of mice in each dose group was increased, but there was a statistical difference compared with the control group (P